Optimization of Savonius Turbine Towards Different Inner Blade Positions to Improve Turbine Performance - Yusuf Dewantoro Herlambang; Supriyo Supriyo; Budhi Prasetiyo; Abdul Syukur Alfauzi; Marliyati Marliyati; Wawan Purwanto; Fatahul Arifin; Zakki Fuadi Emzain (Jurnal POLIMESIN, 2023)
The purpose of this study is to examine the performance of the Savonius turbine on the inner blade position in order to improve turbine efficiency. The blades used are a simplification of the Savonius U/L and the Savonius 1:2 double blade model. This research begins by creating four blade models: a single-blade model, a double-blade model at the blade's tip, a double-blade model at the blade's base, a single-blade model, and a double-blade model along the blades against the wind. The four models are then fitted in the test system for generator performance. Next, the efficiency characteristics of the turbine will be tested against rotation. The test results of the four models were evaluated by comparing each model's efficiency. The results indicate that the Savonius double-blade 1:2 and Savonius U/L turbines achieve efficiencies of 2.42% and 2.1% at 5 m/s and 7 m/s, respectively. At speeds of 5 m/s and 7 m/s, the double-tip position inner blade model increased by 81% and 61%, respectively. The double-tip inner blade variant has the maximum efficiency at 9 m/s, at 3.71 percent. Therefore, the Savonius U/L type vertical axis wind turbine with a 1:2 double blade is the most suited blade model for usage at wind speeds less than 7 meters per second. While the Savonius model with innovations in the inner blade double tip position is suitable for operation at wind speeds greater than 9 meters per second, the Savonius model without such advances is not